Causes, Responses, and Implications of Anthropogenic versus Natural Flow Intermittence in River Networks. (7th December 2022) - Datry, Thibault; Truchy, Amélie; Olden, Julian D; Busch, Michelle H; Stubbington, Rachel; Dodds, Walter K; Zipper, Sam; Yu, Songyan; Messager, Mathis L; Tonkin, Jonathan D; Kaiser, Kendra E; Hammond, John C; et al.
Abstract: Rivers that do not flow year-round are the predominant type of running waters on Earth. Despite a burgeoning literature on natural flow intermittence (NFI), knowledge about the hydrological causes and ecological effects of human-induced, anthropogenic flow intermittence (AFI) remains limited. NFI and AFI could generate contrasting hydrological and biological responses in rivers because of distinct underlying causes of drying and evolutionary adaptations of their biota. We first review the causes of AFI and show how different anthropogenic drivers alter the timing, frequency and duration of drying, compared with NFI. Second, we evaluate the possible differences in biodiversity responses, ecological functions, and ecosystem services between NFI and AFI. Last, we outline knowledge gaps and management needs related to AFI. Because of the distinct hydrologic characteristics and ecological impacts of AFI, ignoring the distinction between NFI and AFI could undermine management of intermittent rivers and ephemeral streams and exacerbate risks to the ecosystems and societies downstream.